Phase I/randomized phase II study of afatinib, an irreversible ErbB family blocker, with or without protracted temozolomide in adults with recurrent glioblastoma. Issue 3 (19th August 2014) - Reardon, David A.; Nabors, Louis B.; Mason, Warren P.; Perry, James R.; Shapiro, William; Kavan, Petr; Mathieu, David; Phuphanich, Surasak; Cseh, Agnieszka; Fu, Yali; Cong, Julie; Wind, Sven; et al.
Abstract: Background: This phase I/II trial evaluated the maximum tolerated dose (MTD) and pharmacokinetics of afatinib plus temozolomide as well as the efficacy and safety of afatinib as monotherapy (A) or with temozolomide (AT) vs temozolomide monotherapy (T) in patients with recurrent glioblastoma (GBM). Methods: Phase I followed a traditional 3 + 3 dose-escalation design to determine MTD. Treatment cohorts were: afatinib 20, 40, and 50 mg/day (plus temozolomide 75 mg/m 2 /day for 21 days per 28-day cycle). In phase II, participants were randomized (stratified by age and KPS) to receive A, T or AT; A was dosed at 40 mg/day and T at 75 mg/m 2 for 21 of 28 days. Primary endpoint was progression-free survival rate at 6 months (PFS-6). Participants were treated until intolerable adverse events (AEs) or disease progression. Results: Recommended phase II dose was 40 mg/day (A) + T based on safety data from phase I ( n = 32). Most frequent AEs in phase II ( n = 119) were diarrhea (71% [A], 82% [AT]) and rash (71% [A] and 69% [AT]). Afatinib and temozolomide pharmacokinetics were unaffected by coadministration. Independently assessed PFS-6 rate was 3% (A), 10% (AT), and 23% (T). Median PFS was longer in afatinib-treated participants with epidermal growth factor receptor (EFGR) vIII-positive tumors versus EGFRvIII-negative tumors. Best overall response included partial response in 1 (A), 2 (AT), and 4 (T) participants and stable disease in 14 (A), 14 (AT), and 21 (T) participants. Conclusions: Afatinib has a manageable safety profile but limited single-agent activity in unselected recurrent GBM patients.